Hubungan antara Tingkat Pengetahuan dengan Pola Perilaku Penanganan Sindrom Premenstruasi di Fakultas Kedokteran Universitas Sebelas Maret - Perdana, David; Danudjo, Tedjo; Wasita, Brian (Nexus Kedokteran Komunitas, 2012)
Background: Premenstrual syndrome is an increased tension and sense ofÂ  the complaints that usually began one week to several days before menstruation. Premenstrual syndrome affects 40% women with 5-10% of them were going to be powerless. Many opinions showed that premenstrual syndrome is Â an usual case, but they almost have a mistake how to handle it. This study aimed to research the relationship between the knowledge level of Premenstrual Syndrome with behavioral patterns of Premenstrual Syndrome handling. Methods: This was an analitic-observasional cross sectional study. The population was medical studentâs 2011 Sebelas Maret University. A sample of 125 people was selected using total sampling. The researchâs instrument used questionnaire about knowledge level of premenstrual syndrome and behavioral patterns of premenstrual syndrome handling. The questionnaire were pre-tested for its validity and reliability. The data were analized by use of Spearman, on SPSS 17.0. Results: Spearman analysis showed a statistically significant relationship between knowledge level and behavioral patterns of premenstrual syndrome handling (P = 0.002). Knowledge level of premenstrual syndrome was weak positive correlation with behavioral pattern of premenstrual syndrome handling (r = 0.272). Conclusions: There were weak positive and statistically significant relationship between knowledge level of premenstrual syndrome with behavioral patterns of premenstrual syndrome handling in Medical Studentâs 2011 Sebelas Maret University. Keywords: Knowledge Level, Behavioral Patterns Handling, Premenstrual SyndromeÂ